A influência das relações simultâneas entre um atacadista e seus fornecedores - Oliveira, Miriam Tiemi Takimura (2016)
In supply chain, many articles in literature support that interorganizational relationships evolve in a growing linear process. These relationships began in the form of a transaction based on price negotiation and they go on until long-term commitment in intense near relationship. However, analyzing the interorganizational relationship as a dyad limits a comprehension of business context. The interorganizational relationship is more complex than two actors, because suppliers are interacting and providing for the same buyer simultaneously. In this sense, this research aims to understand the interference of simultaneous long-term relationship between buyers and suppliers, through their interaction. To develop the research a case study was developed with a focal organization, a wholesaler, and its main long-term consumer goods suppliers. As qualitative research, data collection was based on opening interviews, observations at offices, documents analysis and semi-structured interviews. QDA miner software was used for data analysis. Initially, data was explored on dyad searching convergence and divergence on structural, cognitive and relational dimensions of their speeches, also identifying life-cycle status of the dyad wholesale-supplier. Then, data was analyzed considering similar performance characteristics, pointing trends of transferring restrictive or corrective actions. As main results, simultaneous relations can modify the life-cycle dynamic of buyer-supplier relationship, shortening the initial stages of relationships. The relationship pattern adopted influence when it facilitates isomorphism and homogeneity of dyad relations by transfer actions and positive activities for context.